5(x+3)+12=13-6x

Simple and best practice solution for 5(x+3)+12=13-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+12=13-6x equation:


Simplifying
5(x + 3) + 12 = 13 + -6x

Reorder the terms:
5(3 + x) + 12 = 13 + -6x
(3 * 5 + x * 5) + 12 = 13 + -6x
(15 + 5x) + 12 = 13 + -6x

Reorder the terms:
15 + 12 + 5x = 13 + -6x

Combine like terms: 15 + 12 = 27
27 + 5x = 13 + -6x

Solving
27 + 5x = 13 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
27 + 5x + 6x = 13 + -6x + 6x

Combine like terms: 5x + 6x = 11x
27 + 11x = 13 + -6x + 6x

Combine like terms: -6x + 6x = 0
27 + 11x = 13 + 0
27 + 11x = 13

Add '-27' to each side of the equation.
27 + -27 + 11x = 13 + -27

Combine like terms: 27 + -27 = 0
0 + 11x = 13 + -27
11x = 13 + -27

Combine like terms: 13 + -27 = -14
11x = -14

Divide each side by '11'.
x = -1.272727273

Simplifying
x = -1.272727273

See similar equations:

| (3x+9)+(3x+8)+(3x)=(3x)+(3x)+(4x+5) | | K-7=-13-2k | | 4t+9=(-8)-13 | | 242=x+5-22 | | 405xy+245x^2= | | 6x+308= | | 5x+6x+2+2=3x+5+7x | | -9x-13+11x-25=2 | | (-10)7= | | f(x)=3e^5x | | 100-2P=40+2P | | 100-2P=40 | | log(x+5)=ln(x-3) | | m^2-5m+14=0 | | 5(2x-8)-7x=x+6 | | 40y^9+5y^4= | | 8x-3y+4=0 | | (-1)211= | | 12-m=2m | | 23=7x+3-2x | | y=4x+3x | | 48=x+9+2x | | .6x-.1=4 | | 0=5-n-7 | | 6m-17=-17+2m | | 4x+y=2000000 | | 15x-3=3x-75 | | =hb | | 36y^8+4y^3= | | 12-3(4x-1)=5 | | 3*x^2+7x-15= | | 0.2x-8=-2+x |

Equations solver categories